The impact of abutment manufacturing techniques on reverse torque after cyclic loading and implant-abutment interface fitting: an in vitro study - Alaa Mostafa AboRas; Ahmed Ismail Taha; Nourhan Ahmed Ragheb (BMC Oral Health, 2026)
Abstract Background Screw loosening and implant-abutment interface (IAI) are critical for the long-term success of implant-supported restorations. This study aimed to evaluate the effect of abutment manufacturing technique on reverse torque values and micro-gap measurements at the implant-abutment interface. Methods Thirty dental implant-abutment-crown complexes (Implance, Verdent, Turkey) were randomly allocated into three groups ( n = 10 each) based on the abutment manufacturing technique: Group I—prefabricated titanium abutments (manufacturer-supplied, Implance, Verdent, Turkey; titanium grade 5 ) ; Group II—CAD-CAM-milled titanium abutments; Group III—3D-printed titanium abutments (Selective Laser Melting, SLM). All abutments featured an internal hexagonal connection with platform switching. All crown abutments were tightened to 25 Ncm and subjected to cyclic loading (100 N, 1.6 Hz, 250,000 cycles). Removal torque was measured before and after loading. Micro-gaps at the implant-abutment and abutment-screw interfaces were evaluated using scanning electron microscopy (SEM). Statistical analysis was performed using One-Way ANOVA with Tukey’s Post Hoc test for reverse torque and the Kruskal-Wallis test for gap measurements (α = 0.05). Results After cyclic loading, the 3D-printed (SLM) abutments exhibited significantly higher reverse torque values (11.08 ± 0.11 Ncm) compared to CAD-CAM-milled abutments (6.40 ± 0.79 Ncm) ( P < 0.001). Prefabricated abutments demonstrated the highest post-loading torque values (13.31 ± 0.31 Ncm). All intragroup comparisons showed statistically significant reductions from baseline ( P < 0.0001). No significant difference was found in implant-abutment interface gaps among groups ( P = 0.105). Conclusion Within the limitations of this study, prefabricated abutments demonstrated the highest reverse torque values after cyclic loading. 3D-printed abutments showed significantly greater resistance to torque loss compared to CAD-CAM-milled abutments, approaching the performance of prefabricated abutments. The implant-abutment fit was comparable across groups, suggesting that connection design may be more influential than manufacturing method for macroscopic fit. 3D-printed titanium abutments demonstrated significantly greater mechanical stability than CAD-CAM-milled abutments, approaching the performance of the gold-standard prefabricated abutments. This suggests that additive manufacturing may offer a clinically viable alternative to milling when both customization and mechanical integrity are required. However, clinical studies are needed to confirm these in vitro findings.